Mixings and decays within the Manohar-Wise model. (17th November 2015) - Cheng, Xiao-Dong; Li, Xin-Qiang; Yang, Ya-Dong; Zhang, Xin
Abstract: In this paper, we perform a complete one-loop computation of the short-distance Wilson coefficients for mixings and decays in the Manohar–Wise model, which extends the Standard Model (SM) scalar sector by a colour-octet and weak-doublet scalar. Based on these calculations, combined constraints on the model parameters are derived from the current flavour data, including the mixings, , , , and decays. The future sensitivity to the model is also explored in the observables achievable with of LHCb and of Belle-II data. We find that the Manohar–Wise model could explain the current data, especially when the couplings of the charged colour-octet scalars to quarks are complex, with the resulting being significantly smaller than that of the SM. Finally, we investigate correlations among the two isospin asymmetries and as well as the averaged time-integrated branching ratios some of them are found to be quite strong and could provide, therefore, further insights into the model, once more precise experimental measurements and theoretical predictions for these observables are available in the future.